KERENTANAN DAN KERUSAKAN BERAS LOKAL PROVINSI SUMATERA SELATAN TERHADAP Sitophilus oryzae L. (Coleoptera: Curculionidae) - hendrival hendrival; Fahdra Putri Romadani (Biota, 2018)
The aim of this research is to evaluate the level of susceptibility and damage of rice from local in Musi Rawas Regency, South Sumatera Province to S. oryzae. The experiments revealed that the local rice from Musi Rawas Regency has susceptibility category from moderate to susceptible to S. oryzae infestation. Siam and glutinous rice white are classified are classified as moderate category while rice Ratus, Dayang Rindu, Ambai, Pandak, and Seluang are categorized moderate to susceptible. The Glutinous rice black and Wao are categorized as susceptible to S. oryzae. The susceptibility of local rice in Musi Rawas was affected by the number of F1 S. oryzae (r = 0.966**, P < 0.01) and median development time (r = -0,883**, P < 0.01). The damage of rice affects the rice susceptibility to S. oryzae. The result of correlation analysis showed that there was a very significant positive correlation between susceptibility index and percentage of rice weight loss (r = 0.854**, P < 0,01), percentage of perforated rice (r = 0.955**, P < 0,01) and percentage of rice powder (r = 0.953**, P < 0.01). Rice classified as susceptible such as glutinous rice black and Wao cannot be stored for long periods due to high damage caused by S. oryzae pest during storage rice